1994
DOI: 10.4138/2125
|View full text |Cite
|
Sign up to set email alerts
|

A revised interpretation of Cambrian and Ordovician rocks in the Bourinot belt of central Cape Breton Island, Nova Scotia

Abstract: N ew U-Pb (zircon) data from the northern Boisdale Hills show that rhyolite on Long Island and syenogranite o f the nearby Mount Cameron pluton have similar ages o f 505 ± 3 Ma and 509 ± 2 Ma, respectively. These ages are similar to those known or inferred from some felsic plutonic units elsewhere in central Cape Breton Island and suggest that latest Cambrian to earliest Ordovician igneous activity was widespread in the Bras d'Or terrane. The new dates also suggest that stratigraphic and structural relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…More recently, Lin (1993) and Lynch, Tremblay & Rose (1993) have shown that the Ordovician-Silurian Aspy rocks lie unconformably upon late Proterozoic Bras d'Or rocks, implying that they were part of a single terrane by Ordovician time. Helmstaedt & Tella (1973) reported pebbles of Bras d'Or lithologies in the Cambro-Ordovician overstep sequence, an observation which suggests that the Mira and Bras d'Or terranes were either adjacent (White et al 1994), or amalgamated (Keppie & Dallmeyer, 1989) during Cambrian time. Barr & Hegner (1992) used neodymium isotopic data from Keppie & Dallmeyer, 1989) and terranes in Cape Breton Island according to Barr & Raeside (1989 Proterozoic and Palaeozoic felsic rocks to suggest that different magma sources lay beneath the various terranes in Cape Breton Island throughout Proterozoic and early Palaeozoic times.…”
Section: Geological Settingmentioning
confidence: 95%
“…More recently, Lin (1993) and Lynch, Tremblay & Rose (1993) have shown that the Ordovician-Silurian Aspy rocks lie unconformably upon late Proterozoic Bras d'Or rocks, implying that they were part of a single terrane by Ordovician time. Helmstaedt & Tella (1973) reported pebbles of Bras d'Or lithologies in the Cambro-Ordovician overstep sequence, an observation which suggests that the Mira and Bras d'Or terranes were either adjacent (White et al 1994), or amalgamated (Keppie & Dallmeyer, 1989) during Cambrian time. Barr & Hegner (1992) used neodymium isotopic data from Keppie & Dallmeyer, 1989) and terranes in Cape Breton Island according to Barr & Raeside (1989 Proterozoic and Palaeozoic felsic rocks to suggest that different magma sources lay beneath the various terranes in Cape Breton Island throughout Proterozoic and early Palaeozoic times.…”
Section: Geological Settingmentioning
confidence: 95%
“…1b). These magmatic arc rocks are overlain by Middle Cambrian-Lower Ordovician rocks that include bimodal, within-plate, rift-related volcanic rocks dated at 505 ± 3 Ma (White et al 1994;Keppie et al 1997). This brackets the change from subduction to rifting between 545 and 505 Ma.…”
Section: Tectonic Implications 6a Neoproterozoicmentioning
confidence: 98%
“…Over the past decade, these two views have converged. Thus, White et al (1994) have concluded that the Avalonian overstep sequence of Cambrian age does indeed unconformably overlie their Bras d'Or and Mira terranes. However, they still believe that the two terranes were separate, because Middle Cambrian volcanic rocks in the Bras d'Or terrane are nearly absent in the Mira terrane.…”
mentioning
confidence: 96%
“…The ca. 500 Ma plutons are of granitic composition and may have formed by crustal melting during post-orogenic uplift or during periods of localized extension within the terrane, perhaps linked to the initial stages of separation from Gondwana in the Middle to Late Cambrian (White et al 1994;van Staal and Barr 2012). The variation in level of exposure in Bras d'Or terrane is consistent with the Bras d'Or terrane having been thrust over the Aspy terrane; subsequent erosion thus exposes deeper levels of the terrane near its boundary with the Aspy terrane (Barr et al 1995;Lin 2001).…”
Section: Geological Background Pre-carboniferous Rocksmentioning
confidence: 99%